Synthesis and preliminary evaluation of octreotate conjugates of bioactive synthetic amatoxins for targeting somatostatin receptor (sstr2) expressing cells. Issue 1 (21st October 2021) - Pryyma, Alla; Matinkhoo, Kaveh; Bu, Yong Jia; Merkens, Helen; Zhang, Zhengxing; Bénard, Francois; Perrin, David M.
Abstract : Synthetic amanitin is conjugated to octreotate as a targeting agent: three different linkers and two sites of attachment highlight a robust chemical approach leading to targeted cytotoxicity. Abstract : Targeted cancer therapy represents a paradigm-shifting approach that aims to deliver a toxic payload selectively to target-expressing cells thereby sparing normal tissues the off-target effects associated with traditional chemotherapeutics. Since most targeted constructs rely on standard microtubule inhibitors or DNA-reactive molecules as payloads, new toxins that inhibit other intracellular targets are needed to realize the full potential of targeted therapy. Among these new payloads, α-amanitin has gained attraction as a payload in targeted therapy. Here, we conjugate two synthetic amanitins at different sites to demonstrate their utility as payloads in peptide drug conjugates (PDCs). As an exemplary targeting agent, we chose octreotate, a well-studied somatostatin receptor (sstr2) peptide agonist for the conjugation to synthetic amatoxins via three tailor-built linkers. The linker chemistry permitted the evaluation of one non-cleavable and two cleavable self-immolative conjugates. The immolating linkers were chosen to take advantage of either the reducing potential of the intracellular environment or the high levels of lysosomal proteases in tumor cells to trigger toxin release. Cell-based assays on target-positive Ar42J cells revealed target-specific reduction in viability with up to 1000-fold enhancement in bioactivity compared to the untargeted amatoxins. Altogether, this preliminary study enabled the development of a highly modular synthetic platform for the construction of amanitin-based conjugates that can be readily extended to various targeting moieties.